2021
DOI: 10.2196/29049
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Children With COVID-19 in the United Arab Emirates: Cross-sectional Multicenter Study

Abstract: Background COVID-19 has infected over 123 million people globally. The first confirmed case in the United Arab Emirates (UAE) was reported on January 29, 2020. According to studies conducted in the early epicenters of the pandemic, COVID-19 has fared mildly in the pediatric population. To date, there is a lack of published data about COVID-19 infection among children in the Arabian region. Objective This study aims to investigate the clinical characteristics, laboratory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…21,22 Most studies from neighboring regions extrapolated infant data from a pool of pediatric data and did not dedicate a study characterizing SARS-CoV-2 in infants alone. [23][24][25][26] In a multicenter study from Israel utilizing a prospective surveillance network including 20 of the country's 26 hospitals, 75 infants were examined, with 96% of the pooled cohort having described a benign disease course and favorable outcomes. 27 In another multicenter prospective study from Turkey 28 examining data from 24 neonatal ICUs, 37 symptomatic neonates were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Most studies from neighboring regions extrapolated infant data from a pool of pediatric data and did not dedicate a study characterizing SARS-CoV-2 in infants alone. [23][24][25][26] In a multicenter study from Israel utilizing a prospective surveillance network including 20 of the country's 26 hospitals, 75 infants were examined, with 96% of the pooled cohort having described a benign disease course and favorable outcomes. 27 In another multicenter prospective study from Turkey 28 examining data from 24 neonatal ICUs, 37 symptomatic neonates were included.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies from neighboring regions extrapolated infant data from a pool of pediatric data and did not dedicate a study characterizing SARS-CoV-2 in infants alone. 23–26…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high levels of CRP and lactate dehydrogenase were significantly associated with symptomatic children. History of contact with family or household member was reported in the majority of infected patients ( Ennab et al, 2021 ). In Iraq, Salih et al, found that fever was the common symptom detected in children with COVID-19.…”
Section: Childrenmentioning
confidence: 99%